2021
DOI: 10.1302/2046-3758.109.bjr-2020-0443.r1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following surgical management of femoroacetabular impingement: a systematic review and meta-analysis of different surgical techniques

Abstract: Outcomes following different types of surgical intervention for femoroacetabular impingement (FAI) are well reported individually but comparative data are deficient. The purpose of this study was to conduct a systematic review (SR) and meta-analysis to analyze the outcomes following surgical management of FAI by hip arthroscopy (HA), anterior mini open approach (AMO), and surgical hip dislocation (SHD). This SR was registered with PROSPERO. An electronic database search of PubMed, Medline, and EMBASE for Engli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Bony femoral impingement on the anterior-inferior (femoral 4 to 5 o'clock position) aspect of the femoral neck could be important for patients undergoing hip arthroscopy or open hip preservation surgery (surgical hip dislocation or anterior mini open approach). 48 Planning of cam resection or rim trimming before hip arthroscopy should be evaluated carefully in FAI patients with decreased FV who report hip pain in flexion, especially for patients with pincer-type FAI or mixed-type FAI (because of the low impingement-free flexion). Impingement simulation is based on patient-specific 3D models of the hip joint.…”
Section: Discussionmentioning
confidence: 99%
“…Bony femoral impingement on the anterior-inferior (femoral 4 to 5 o'clock position) aspect of the femoral neck could be important for patients undergoing hip arthroscopy or open hip preservation surgery (surgical hip dislocation or anterior mini open approach). 48 Planning of cam resection or rim trimming before hip arthroscopy should be evaluated carefully in FAI patients with decreased FV who report hip pain in flexion, especially for patients with pincer-type FAI or mixed-type FAI (because of the low impingement-free flexion). Impingement simulation is based on patient-specific 3D models of the hip joint.…”
Section: Discussionmentioning
confidence: 99%
“…9 The success in addressing FAIS by surgical hip dislocation has been shown to be equivalent to hip arthroscopy in both survivorship and hip-specific patient reported outcomes at mid-term follow-up in a systematic review. 29,30 Steppacher et al 31 has shown an 80% 10year survivorship after surgical hip dislocation for the treatment of FAIS. More recently in a propensitymatched analysis of hip arthroscopy versus surgical hip dislocation, Nepple et al 32 reported no significant difference in postoperative patient reported outcomes after surgery, revision to total hip arthroplasty (surgical hip dislocation 3.1% compared to arthroscopy 0%, P ¼ .12), or persistent symptoms (surgical hip dislocation 24.4% compared to arthroscopy 21.9%, P ¼ .55).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the pooled incidence of surgical complications was 1%, which is almost the same as the overall complication rate after hip arthroscopy for FAIS in adolescents, 29 and slightly lower than the pooled rate of all complications (4%) in adults. 1 …”
Section: Discussionmentioning
confidence: 99%